Repercussions of DDoS Attack on MANET based Healthcare Sector Routing Protocols Performance and ANOVA Assessment - Ashu Gautam, Rashima Mahajanb, Sherin Zafarc (International Journal of Advanced Science and Technology, 2020)
The pandemic condition created by COVID -19 across the globe witnessed the usage of technology in the dynamic fields, majorly wirelessly based networks such as wireless mesh networks (WMN) and Mobile Ad-hoc networks (MANETS).As remote monitoring forms the basis of smart healthcare environment, therefore, MANET protocols such as Ad-hoc On Demand Vector (AODV), Secure AODV (SAODV) and Hybrid Wireless Mesh Protocol (HWMP) are simulated through this research study. The success of remote monitoring of patients health along with consequent analysis are very much reliant on message passing approach of various routing protocols. It is essential to showcase the effect of various attacks affecting the routing methodology of these protocols. This research study analyses AODV, SAODV and HWMP under DDoS attacks through various simulation parameters with its legal implications also. In this research study, most suitable routing protocols to handle DDoS attacks are simulated and estimated in terms of normalized routing load (NRL) in the state of changing nodes. This aids in providing implications to enhance existing protocols and alleviate the consequences of DDoS investigation by such attacks. The performance of AODV, SAODV and HWMP are compared using NS-2 and tabularized.We use the ANOVA test is used to find out correctness sof the result and finally concluded the best suited routing protocol for handling the data packets,in terms of evaluation metrics namely Normalized Routing Load(NRL) and could be considered as much less vulnerable against DDoS attacks prevailing in healthcare sector